The Crystallinity Control of Polymer Donor Materials for High-Performance Organic Solar Cells - Qiu, Dingding; Adil, Muhammad Abdullah; Lu, Kun; Wei, Zhixiang (Frontiers in Chemistry, 2020)
Bulk heterojunction organic solar cells (BHJ OSCs) can be regarded as one of the most promising energy generation technologies for large-scale applications. Despite their several well-known drawbacks, the devices where polymers are employed as the donor are still leading the OSC universe in terms of performance. Such performance generally depends upon various critical factors such as the crystallinity of the material, the crystallization process during the film formation and also the final film morphology. Despite a few reviews on the structure of the polymer donor materials and device performance, not enough attention has been paid towards the crystallinity problem. Herein, the structure and crystallinity of the representative polymer donor materials and the corresponding device properties have been briefly reviewed. Furthermore, several typical methods for controlling the crystallinity of materials have been summarized and illustrated as well. Moreover, the obstacles lying in the way of successful commercialization of such polymer solar cells have been systematically discussed. The in-depth interpretation of the crystallinity of the polymer donors in this article may stimulate novel ideas in material design and device fabrication.